Inversion polymorphism in laboratory strains and natural samples of Drosophila sturtevanti (saltans group, sturtevanti subgroup) - Hosaki Kobayashi, Marlene Kiyoni [UNESP]; De Campos Bicudo, Hermione Elly Melara [UNESP] (My University, 1997)
Drosophila sturtevanti (37 strains) showed eighteen inversions, five new and thirteen previously described. Among these strains, 24 were maintained for seven to 21 years under laboratory conditions, eight for less than 1 year, and six were natural samples analysed in the first generation after collection. Flies from natural samples were the most polymorphic in the number of different inversions as well as in the frequency of flies bearing heterozygous inversions. In all cases, chromosome III presented the greatest number of inversions, and most of them occurred in strains from the Amazonian region. The data obtained were consistent with the hypothesis that the inversion variability of a species is proportional to the variability of its habitats.
Keywords: Chromosome inversions; Drosophila; Inversion polymorphism